GASTRITIS MASKING LATE SYMPTOMS OF MUSHROOM POISONING IN A TEENAGER. A CASE REPORT - Claudia Olaru; Lucian Stefan Burlea; Tamara Solange Rosu (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study. Mushroom poisoning in children is an infrequent but challenging problem for parents and pediatricians. In Romanian rural areas, picking mushrooms and eating them is a common practice that may lead to severe or even fatal events. Case report. We report the case of a 14 years old teenager with late symptoms caused by the ingestion of a small amount of mushrooms, initially admitted into the gastroenterology unit for gastritis. A 14 years old female teenager presented with vomiting and gastric pain that started two days prior to admission. Clinical examination showed generally impaired status, bilious vomits and colicative gastric pain. History revealed that 72 hours before all family members (both parents and four brothers) had eaten home-cooked mushrooms picked by the father. Laboratory data showed fulminant hepatic failure (ASAT=5141 U/L, ALAT=6520 U/l, LDH=2520U/l), hyperammonemia, mixed hyperbilirubinemia and normal renal function; the prothrombin time and activated partial thromboplastin time were prolonged. All family members were symptom-free and their laboratory tests were within normal ranges. The patient was transferred to the toxicology unit, where supportive therapy was started with large amounts of IV fluids, IV benzyl penicillin, proton pump inhibitors, arginine infusion and N-acetylcysteine. The evolution was both clinically and biologically favorable, with normalization of hepatic enzymes within two weeks. Conclusions. In our case, the ingestion of mushrooms produced late gastrointestinal symptoms and fulminant liver failure. In Romania, conducting public information campaigns regarding the poisonous nature of wild mushrooms could be an effective prevention method.